N‐terminal pro–brain natriuretic peptide and cognitive decline in older adults at high cardiovascular risk. Issue 2 (9th July 2014) - Wijsman, Liselotte W.; Sabayan, Behnam; van Vliet, Peter; Trompet, Stella; de Ruijter, Wouter; Poortvliet, Rosalinde K. E.; van Peet, Petra G.; Gussekloo, Jacobijn; Jukema, J. Wouter; Stott, David J.; Sattar, Naveed; Ford, Ian; et al.
<x xml:space="preserve">Abstract</x> Objective Elevated levels of N‐terminal pro–brain natriuretic peptide (NT‐proBNP) are associated with cognitive impairment, which might be explained by cardiovascular diseases or risk factors. The aim of this study was to investigate the association of NT‐proBNP with cognitive function and decline in older adults at high risk of cardiovascular disease. Methods We studied 5, 205 men and women (mean age = 75 years) who were recruited into the PROspective Study of Pravastatin in the Elderly at Risk. All participants had pre‐existing cardiovascular disease or risk factors thereof. Four domains of cognitive function were tested at baseline and repeated during a follow‐up period of 3.2 years. Results Participants with higher NT‐proBNP (≥450ng/l) had worse baseline cognitive function, including reaction time (mean difference high vs low group = 3.07 seconds, 95% confidence interval [CI] = 0.83 to 5.32), processing speed (−1.02 digits coded, 95% CI = −1.65 to −0.39), and immediate memory (−0.13 pictures remembered, 95% CI = −0.29 to 0.04). There was no significant difference in delayed memory (−0.14, 95% CI = −0.38 to 0.10) between the NT‐proBNP groups. Participants with higher NT‐proBNP had a steeper cognitive decline, including reaction time (mean annual change high vs low group = 0.60 seconds, 95% CI = 0.14 to 1.07), processing speed (−0.15 digits coded, 95% CI = −0.25 to −0.05), immediate memory (−0.05 pictures remembered, 95% CI = −0.09 to 0.00), and delayed memory (−0.05 pictures remembered, 95% CI = −0.11 to 0.01). Associations were independent of cardiovascular diseases and risks. Interpretation Higher NT‐proBNP associates with worse cognitive function and steeper cognitive decline, independent of cardiovascular diseases and risks. Further studies to unravel the underlying mechanisms are warranted. Ann Neurol 2014;76:213–222